Air Pollution Quality Monitoring System Using Internet of Things for Smart Cities (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Internet of Things (IoT) Based Air Pollution Monitoring System is used to monitor the Air Quality over a web server using Internet. It will trigger an alarm when the air quality goes down beyond a certain level, means when there is sufficient amount of harmful gases present in the air like CO2, smoke, alcohol, benzene, NH3 and NOx.Pollution deaths are growing every year, and air pollutants is the primary contributor to those deaths. Occasionally, emission levels have risen due to several causes, such as the rise in population, increased use of automobiles, industrialization and urbanisation, which have a significant influence on the wellbeing of the people. To observe the situation this work includes anair pollution monitoring system which is an Internet of things using sensors based system,where we track quality of air through a web server on the Internet and generate warning about the air quality goes above a firm threshold, it implies when sufficient hazardous gas is present in the air such as benzene, NH3, smoke, CO2 and alcohol.The growth of business and Speedy human population urbanisation has horribleimpactupon worldwide air condition. in long-time period exposure to air pollution cause chronic heart and lung diseases, dangerously affecting human health. Thousands of factories and billions of cars launch large quantities of pollution into the air each day. so, tracking the air pollution has come to be important. In this paper, the development of an Internet of Things based air quality monitoring platform is presented and analize the performance of air quality monitoring system.